Inflation Targeting in New Zealand: Does Policy Match Practice? - Collins, Taylor (Journal of Applied Business and Economics, 2022)
In this paper, I primarily seek to empirically test whether or not the Reserve Bank of New Zealand (RBNZ) is systematically acting in accordance with their stated monetary policy goal of achieving medium run price stability. In this pursuit, I utilize a series of threshold regressions and vector autoregressions to test responsiveness of the Official Cash Rate to projected inflation deviations from the RBNZ’s stated inflation target. Comfortingly, I uncover strong evidence that the RBNZ is in fact systematically setting policy in accordance with their stated policy objective of medium run price stability.